(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
A healthy and clear facial impression plays the important part for the development of the personality. Since ages, Acne vulgaris has always been one of the most burning problem of the adolescents. It affects the most prominent part of our body, the face. Among the multifactorial etiology of acne hormonal imbalance and infections are most important. Acne is a cutaneous pleomorphic disorder of the pilosebaceous unit involving abnormalities in sebum production and is characterized by both inflammatory (papules, pustules and nodules) and non-inflammatory (comedones, open and closed) lesions. Propionibacterium acnes is responsible for the development of acne vulgaris. Acne Vulgaris can be correlated with Mukhadushika or Yuvanpidika on the basis of similarity in the etiopathogenesis, symptoms, treatment and complication. In Ayurveda it is the Shalmali thorn like eruptions on the face of adolescent due to vitiation of Kapha, Vata and Shonita. Allopathic treatment includes treatment for all forms of acne as topical retinoids and benzoyl peroxide, oral antibiotics, steroids etc. But these causes serious adverse effects. So it is necessary to find out effective and safe treatment for Acne Vulgaris. Ayurveda is for it which plays important role through its principles i.e. Shodhana, Shamana and Nidanparivarjana. As described by various Acharya the Shodhanachikitsa includes Vamana, Virechana and Shiravedha. Among Shodhana, Virechana process is the safe and effective treatment, providing long lasting result for better life of patient.